Suitability of Land Plants For yam ( Pachyrrizus erosus L . ) In District Koto Padang Tangah - Tilawati, Tilawati; Dasrizal, Dasrizal; Thesiwati, Aslan Sari (STKIP PGRI Sumbar, 2013)
The study was conducted Husband New Articles 1 goal ) determine the characteristics of Appropriate Land for Plant jicama 2 ) determine which unit Appropriate Land for yam plant in Padang Tangah Koto district . Land units NO FUNDS The research area is comprised of 63 units of English Land And The sample was taken only 4 units Land Only.Sampling technique is using sampling techniques wilayah ( area sampling ) based FUNDS The Land unit variation . Sampling New Articles How to choose traits - traits population The ADA ( purposive sampling ) in which the sample was taken as the One sample representing each variation unit Land That meets the criteria to be used Land Plant yam . New Articles reason Sampling Method initials BECAUSE FUNDS The same unit of land is assumed to have the same characteristics Yang anyway , so the Land forms The same unit can be represented nil By Land unit . The data analysis used is descriptive analysis in the form of tables - Land characteristics BETWEEN comparison table ( texture , pH , organic materials , structures , Rainfall , temperature , slope ) compared to New Article compliance level land for yam plants .Results showed that : 1 ) there are differences in the characteristics of the Land Organic materials FUNDS One unit of land and per unit of rainfall FUNDS The ADA in the District Land Tangah Koto Padang , 2 ) the presence of the suitability of land for plant diversity in Sub yam Tangah Koto Padang . Land Unit New Article FUNDS As per the conditions contained research area is the land form plains unit FUNDS Fluvial ( F1 ) New Media Unit Land F1.I.Tg.Qal.lat , pyroclastic flow fan ( V2 ) V2 New Media unit of land . II . Tg . Qal . Lat , volcanic hills ( V3 ) New Article lahanV3 unit . II . Tg . Qal . Lat , volcanic mountains ( V4 ) V4 Land New Media unit . II . Sw . Qtau . Lat